2020
DOI: 10.1186/s12935-020-1129-y
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNASNHG17 promotes the progression of breast cancer by sponging miR-124-3p

Abstract: Background: Small nucleolar RNA host gene 17 (SNHG17), a novel cancer-related long noncoding RNA (lncRNA), was reported to be responsible for processing and developing in several cancers. Nonetheless, the clinical significance and biological function of SNHG17 in human breast cancer (BC) remain rarely known. Materials and methods: 58 pairs of BC tissues and adjacent non-cancerous tissues were harvested to measure SNHG17 expression levels. SNHG17 was knockdown to study its biological behavior in BC cells. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…6,7 Studies have revealed that multiple lncRNAs are dysregulated in many types of cancers, and that lncRNAs are closely associated with the diagnosis and prognosis in cancer patients, [8][9][10][11][12] including BC. 7,13,14 lncRNAs have been implicated in the regulation of various cancer hallmarks, including proliferation, metastasis, apoptosis, and chemoresistance. 6,12,15 lncRNA LOXL1-AS1 has been reported to promote the invasion and metastasis of BC cells by antagonizing the expression and activity of microRNA (miR)-708-5p.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Studies have revealed that multiple lncRNAs are dysregulated in many types of cancers, and that lncRNAs are closely associated with the diagnosis and prognosis in cancer patients, [8][9][10][11][12] including BC. 7,13,14 lncRNAs have been implicated in the regulation of various cancer hallmarks, including proliferation, metastasis, apoptosis, and chemoresistance. 6,12,15 lncRNA LOXL1-AS1 has been reported to promote the invasion and metastasis of BC cells by antagonizing the expression and activity of microRNA (miR)-708-5p.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SNHG17 can act as a ceRNA to sponge miR-124-3p and miR-506-3p. 20 , 21 In OVCAR-3 cells, we found that silencing SNHG17 caused a slight increase in miR-124-3p (about 30%), which was much lower than that in miR-214-3p (about 300%), and had almost no effect on the expression of miR-506-3p ( Figure S2 C). These results indicate that SNHG17 can regulate miR-214-3p expression through working as a ceRNA in OC.…”
Section: Resultsmentioning
confidence: 95%
“…LncRNA SNHG17 is recently indicated to play a critical role in the development and progression of several types of human malignancies. [11][12][13][14] For example, Xu et al showed that gene ampli cation drove SNHG17 promoted proliferation and invasion and inhibited apoptosis of NSCLC cell lines. [14] In gastric cancer, Han and his coauthors found that lncRNA SNHG17 was upregulated by Helicobacter pylori infection, a well-known risk factor for gastric cancer, and high expression of SNHG17 was related to dismal OS in patients with stomach cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, aberrant expression of SNHG17 has been suggested to play vital roles in the development and progression of human carcinomas, such as gastric cancer, prostate cancer, non-small cell lung cancer (NSCLC), and breast cancer, etc. [11][12][13][14] However, to the best of our knowledge, the biological roles and underlying molecular mechanisms of SNHG17 in RCC remain unclari ed.…”
Section: Introductionmentioning
confidence: 99%